Analisis Kebutuhan Perubahan Pada Home Industri Di Masa Covid 19 (Studi Kasus Vivana Konveksi Medan) - Rahmanda, Vina; Aslami, Nuri (Universitas Labuhanbatu, 2022)
This study aims to find out how the clothing convection home industry performs the needs of change by looking at business opportunities that occur in the covid 19 era due to declining demand. This study uses a qualitative method with a case study approach. With descriptive method, the data was collected by first observation and then followed by interviews by business owners of home industry convection Vivana Medan. Data obtained directly in the field. The results showed that the need for changes during the COVID 19 Pandemic was successfully implemented with project planning.